Mineralogia, química e avaliação da fertilidade potencial de fragmentos cerâmicos de sítio de terra preta: Caxiuanã, Juruti, Barcarena e Quebrada Tacana. - SILVA, Glayce Jholy Souza da (Universidade Federal do Pará, 2019)
Small areas with Amazonian Dark Earth (ADE) soils stretch across the Amazon region. Among its most striking features stand out the high nutrient content and contain human occupation remains. Ceramic fragments are the most frequently recovered in these soils. The high content of phosphorus in the ADE has long been reported and recent studies show that the fragments also contain them. In order to relate the fertility of the ADE to the abundant presence of ceramic fragments, this work aimed to investigate the chemical and mineralogical composition as well as evaluating the fertile character of the fragments and their ability to release nutrients to the soil. For this goal it was selected 44 ceramic fragments collected at four sites: Barcarena, Caxiuanã, Juruti and Tacana at Leticia in Colombia. The mineralogical analysis was performed by x-ray diffraction (XRD), and the determination of antiplásticos and textural aspects of optical microscopy and scanning electron microscopy. The composition was determined by ICP-MS via alkaline fusion. The extraction of the nutrients phosphorus, potassium, calcium, copper, zinc, manganese, magnesium, iron and sodium was performed with Mehlich 1. In the desorption tests were used only suspensions containing citric acid (pH 4.5-5.5) in allusion to the presence of humic acids in TPA soils. The fragments contain quartz and metakaolin as common stages and distinguish each other by the presence of talc, calcite and hematite fragments in Raimundo site; chlorite in Quebrada Tacana and Barcarena; cristobalite in Raimundo and Quebrada Tacana. The high content of SiO2 and Al2O3 agree with the dominant mineralogy, quartz and kaolinite; K2O composes the feldspars and micas, especially in Juruti; CaO are in low concentrations, except for Raimundo because of the presence of shells in both fragments and in the soil; whereas P2O5 reached values of 0.9, 2.9 and 4.7% in the fragments of the Raimundo, Quebrada Tacana and Juruti sites, respectively, without finding crystalline mineral phase; in Barcarena is virtually absent. The microcrystalline nature of the metakaolinite plasmic observed under an optical microscope, constitutes the matrix. The amorphous nature is indicated by the high background observed in most diffraction patterns and the classification as metakaolinite as permitted by the high content of SiO2 and Al2O3; together they represent more than 50% of bulk composition. The tempers ranged from according to the origin of the fragments. Cariape is common in the fragments of Raimundo, Quebrada Tacana and Barcarena; cauixi in Juruti’s fragments; coal in Quebrada Tacana, while shells are restricted to fragments of Raimundo. The results for fertility showed that the fragments of Quebrada Tacana and Juruti stand out in the contents of available P reaching 1045 e 2250 mg/dm³, respectively, while very low concentrations of this nutrient were found in Barcarena fragments. With reference to exchangeable K all fragments showed high contents, the largest variations were found for Zn, Mg, Mn, while exchangeable Ca stood out in fragments of the Raimundo site. Tests for desorption prove that the fragments release nutrients, especially phosphorus, found in high contents in samples from the Quebrada Tacana and Juruti, and even nutrients like calcium and magnesium, present in low concentrations also undergo desorption. These results indicate that ceramic vessels were made from basic clayey raw material, common, represented by kaolinite and quartz, in other words clays. The mineralogical variations are reflections of local geology and the different tempers added to the ceramic. The kaolinite present in some fragments is a new-formed product from the changes experienced by the fragment rich in SiO2 and Al2O3. The metakaolinite is a product of burned of raw material (rich in kaolinite). Different tempers added could be related to preference or availability of each people in the region, whose importance for the manufacture of ceramic materials was known. The nutrient contents of the fragments are favorable to agriculture, especially phosphorus (except in Barcarena) and potassium. Moreover, they are able to release them in the presence of an organic acid, which is common product of decomposition of organic matter and is exuded by the roots of some plant species, indicating that the fragment can assume the same behavior in the soil.